Characteristics of members of IGT family genes in controlling rice root system architecture and tiller development - Zhao, Jianping; Jiang, Lihui; Bai, Hanrui; Dai, Yuliang; Li, Kuixiu; Li, Saijie; Wang, Xiaoran; Wu, Lixia; Fu, Qijing; Yang, Yanfen; Dong, Qian; Yu, Si; et al. (Frontiers in Plant Science, 2022)
Root system architecture (RSA) and tiller are important agronomic traits. However, the mechanisms of the IGT family genes regulate RSA and tiller development in different rice varieties remain unclear. In this study, we demonstrated that 38 rice varieties obtained from Yuanyang Hani’s terraced fields with different RSA and could be classified into six groups based on the ratio of root length and width. We found a positive correlation between RSA (including root width, length and area) and tiller number in most of rice varieties. Furthermore, the IGT family genes DRO1, LAZY1, TAC1 and qSOR1 showed different expression patterns when rice grown under irrigation and drought conditions. Moreover, the qSOR1 gene had higher levels in the roots and tillers, and accompanied with higher levels of PIN1b gene in roots when rice grown under drought environmental condition. DRO1 gene had two single nucleotide polymorphisms (SNPs) in the exon 3 sequences and showed different expression patterns in the roots and tillers of the 38 rice varieties. Overexpression of DRO1 with a deletion of exon 5 caused shorter root length, less lateral roots and lower levels of LAZY1, TAC1 and qSOR1. Further protein interaction network, microRNA targeting and co-expression analysis showed that DRO1 plays a critical role in the root and tiller development associated with auxin transport. These data suggest that the RSA and tiller development are regulated by the IGT family genes in an intricate network way, which is tightly related to rice genetic background in rice adapting to different environmental conditions.